2008
DOI: 10.1016/j.jnt.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Shrinking the period lengths of continued fractions while still capturing convergents

Abstract: Here we prove that every real quadratic irrational α can be expressed as a periodic non-simple continued fraction having period length one. Moreover, we show that the sequence of rational numbers generated by successive truncations of this expansion is a sequence of convergents of α. We close with an application relating the structure of a quadratic α to its conjugate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 4 publications
(7 reference statements)
1
26
0
Order By: Relevance
“…We establish our result by extending some of the arguments of [1], in this new context and making appropriate adjustments.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…We establish our result by extending some of the arguments of [1], in this new context and making appropriate adjustments.…”
Section: Introductionmentioning
confidence: 72%
“…In [1] Burger et al prove that every real quadratic irrational α can be expressed as a periodic non-simple continued fraction having period length one. Moreover, it is proved that the sequence of rational numbers generated by successive truncations of this expansion is a sequence of convergents of α, For further references on the subject, see also [3], [2] and [4].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this paper is to prove a GaussKuzmin type problem for Ncontinued fraction expansions introduced by Burger et al [3]. In order to solve the problem, we apply the theory of random systems with complete connections by Iosifescu [9].…”
Section: Introductionmentioning
confidence: 99%
“…}, with T 0 N (x) = x. By the very definitions, Burger et al proved in [3] that any irrational 0 < x < 1 can be written in the form where a n 's are non-negative integers. We will call (1.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Edward Burger and his co-authors showed in [3] that a similar result also holds if a n = N for all n ≥ 1 and for infinitely many positive integers N . However, in their result, the continued fraction expansion (which is now a so-called "N -expansion") is not necessarily proper, i.e., we need not have that b n ≥ N for all n ≥ 1.…”
mentioning
confidence: 80%